Emergence of Dynamical Dissipative Structures in a Bistable Spin Crossover Solid Under Light: Experience and Theory. Issue 9 (25th July 2018) - Boukheddaden, Kamel; Sy, Mouhamadou; Varret, François
Abstract: In this article, the basic spatiotemporal theory elucidating the physical conditions leading to the emergence of dissipative structures and pattern formation in spin‐crossover solids under light causing their photo‐heating is outlined. In this context, the spatiotemporal properties of the spin‐crossover (SC) transition are described as a reaction diffusion process. The time evolution of the spin state (the high spin fraction) is coupled to the spatiotemporal properties of temperature inside the lattice, accounting for: (i) the crystal photo‐heating, (ii) the coupling to thermal bath, and (iii) the thermal diffusion. It is demonstrated that around well‐defined unstable regions, this system leads to the emergence of nonstationary Turing patterns, dynamic dissipative structures, and autocatalytic oscillations of which an experimental example is provided on the SC single crystal ([{Fe(NCSe)(py)2 }2 ( m ‐bpypz)]). These results pave the way to a new fertilized field in the quest of nonlinear dynamics and morphogenesis in molecular switchable solids undergoing first‐order phase transitions. Abstract : This article deals with the direct observation using optical microscopy of the emergence of Turing patterns and autocatalytic behavior of complex high‐spin low‐spin structures in spin‐crossover solids under light. These observations have been modeled using two nonlinear coupled reaction diffusion equations, in which the high spin fraction and the temperature play the role of the activator and the inhibitor, respectively.